Development of Automated IoT-Based Monitoring Multilevel Parking System - Kamarul Azlan, Saifullah; Sy yi, Sim (Progress in Engineering Application and Technology, 2021)
The Smart Multilevel-parking system is the parking system that proposed to implement in Malaysia to prevent the problem limited parking lot. The smart multi-level parking system is the parking system that in Malaysia can be advanced in transport services technology. The problem cause of the urban city with limited parking space and hard to pay at the counter. The purpose of the project is to study the needs and constraints of multi-parking system and to proposed the fully automated of multi-parking system to suit the system in Malaysia. To enhance this project, the application of IoT-based monitoring system with Blynks apps is used in this project. As the prototype and mechanical portion, the proposed Smart Multilevel-parking system is used to help and finance the cost of materials. This project will work with IoT and verify with the prototype.